The Effect of Educational Video About Maternal Health Related to COVID-19 to Knowledge Level of Medical Student - Aulika Alya Paramesti; Putri Sekar Wiyati; Diah Rahayu Wulandari (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background : There have not been many cases of COVID-19 infection in pregnant women before, during and after gavebirth, so knowledge about COVID-19 infection in pregnancy and the fetus is still limited. This research is expected to provide basic data for further studies and provide new knowledge, especially regarding maternal health related to COVID-19, considering that currently COVID-19 is a new type of virus and is currently a pandemic.Objectives : This study aimed to to determine the effect of educational videos about maternal health related to COVID-19 on the level of knowledge of Medical Students.Methods : This research was a pre-experimental research design design using the form of a "One Group Pretest-Postest only" design (without a control group). Statistical analysis using the Wilcoxon Test.Results: The results shows that from 38 respondents after being given education through video media, it was found that 36 (95%) of respondents had increased knowledge, 2 (5%) had fixed knowledge, and there were no respondents whose knowledge had decreased, so there was a significant difference in knowledge before and after being given education through video.Conclusion: The study result showed that there is a significant difference in knowledge about maternal related to COVID19 before and after being given education via video and it can be concluded that there is an effect of educational videos on Maternal Health related to COVID19. Keywords :  Educational Video, Maternal, COVID-19, Knowledge.